Angelica Cappelletto Duse - Pagani, Maria Pia (Drammaturgia, 2024)
Angelica Cappelletto is the wife of Alessandro Vincenzo Duse and the mother of Eleonora. She has acted in secondary theatre companies without excelling in her profession, reaching only once the role of prima attrice.